The Depositors' Guaranty Law of Oklahoma - Webster, W. C. (Journal of Political Economy, 1909)
Durinlg the recent presidential campaign the people of this country, especially those in the W'est, heard a great deal about the guaranteeing of blank deposits. The idea is not a new one. It has frequently been advocated in the past, and a few of our states long ago tried the experiment: New York in I829, Vermont in I83I, and Michigan in 1836. In all these cases the experiments ended disastrously. In fact, it would be difficult to find a single example of the successful operation of such a scheme in this or any other country. Yet the advocates of the proposed plan, with varying degrees of inaccuracy, cite Germany's siystem of municipal savings banks, Canada's 5 per cent. guaranty of bank notes, Georgia's "chain-of-banks" system, and other unwarranted analogies, as ample evidence of their wisdom. Now comes the new state of Oklahoma, and under the inspiration of Mr. Bryan and Governor Haskell, the world is given another guaranty law-a sure preventive of any future financial disasters. Fortunately this is the only recent measure of the kind thus far enacted, but it is greatly to be feared that it will not long retain its solitary position, unless the spread of the false doctrine throughout the West is speedily checked.